The Influence of SME’s Collaboration on SME Innovation Capabilities - Susanta, Susanta; Utomo, Humam Santosa; Fitriyani, Lita Yulita; Rahmawati, Keny (RSF Conference Series: Business, Management and Social Sciences, 2021)
The ability to innovate is indispensable in a turbulent external environment. SME’s in Bantul Yogyakarta formed a group of non-formal organizations to overcome business difficulties during the pandemic by increasing business innovation capabilities. This study also aims to examine the effect of SME’s collaboration on innovation capability during the COVID-19 pandemic. This research is important to do obtain information on the effectiveness of SME collaboration to create innovation and achieve SME performance. During a pandemic where the business environment is increasingly dynamic, this research is increasingly needed to obtain an effective collaboration model. The research was conducted on 100 local processed food SME’s using a quantitative approach. The research instrument was in the form of a questionnaire equipped with interviews to obtain comprehensive data and information. The analytical tool used is WarpPLS. The results show that SME’s collaboration has a significant effect on innovation capabilities.